Effect of Levosimendan on Diastolic Function in Patients Undergoing Coronary Artery Bypass Grafting: A Comparative Study. Issue 2 (August 2015) - Malik, Vishwas; Subramanian, Arun; Hote, Milind; Kiran, Usha
Abstract : Purpose: To compare the efficacy of levosimendan with nitroglycerin in patients with isolated diastolic dysfunction undergoing coronary artery bypass grafting. Procedure: Thirty patients with isolated diastolic dysfunction undergoing on-pump coronary artery bypass grafting were randomized into 2 groups receiving levosimendan or nitroglycerin infusion. The infusion was started before sternotomy and continued in the postoperative period. Perioperatively, diastolic function was serially evaluated at 3 different time points using echocardiography. N-terminal fragment of pro–B-natriuretic peptide (NT-proBNP) levels were measured in both the groups. Results: There was a significant improvement in diastolic function as measured by isovolumic relaxation time ( P = 0.0001, P = 0.001) and deceleration time ( P = 0.0001, P = 0.0001) in the levosimendan group from the baseline in patients with impaired relaxation. Similarly, tissue Doppler imaging also revealed an improvement from the baseline in patients with a pseudonormal pattern ( P = 0.018, P = 0.001). Furthermore, there was a significant improvement in the above parameters when compared with the nitroglycerin group. The NT-proBNP levels also demonstrated a similar pattern between the 2 groups ( P = 0.03, P = 0.02) when levosimendan was compared with nitroglycerin in patients with a pseudonormal pattern on echocardiography. Conclusions: Levosimendan is superior to nitroglycerin in improving diastolic function irrespective of coronary revascularization.